Operational value creation in private equity: art or science? - Desmcht, Annick E (IE University, 2019)
We examine how executive teams of Private Equity portfolio companies deliver superior returns through their strategic and daily operational decisions and actions. We run a comparative multiple case study of four companies, each of which went through a successful Private Equity (PE) investment cycle, and interview key members of the executive team and board as well as cross-industry experts. Using a qualitative, inductive process methodology, we match patterns between cases to tease out similarities and variance across cases and to develop a typology of actions maximizing the enterprise value at exit of the investment. We structure those actions in four distinct dimensions, which mirror the key stages of an investment, to develop a model for Private Equity operational value creation. Finally, we use dynamic capabilities and agency theories as an interpretive lens to analyze value creation in the specific context of Private Equity portfolio companies.
Creación de valor operativo en private equity: ¿arte o ciencia?
Keywords: Agency theory; Dynamic capabilities; Leveraged buyouts; Operational value creation; Private Equity; Teoría de la agencia; Capacidades dinámicas; Adquisiciones apalancadas; Creación de valor operativo; Capital privado